Dendritic segregation measuring method for large ingot type hot work die steel
Through heat treatment and simple chemical corrosion process, combined with scanning electron microscopy analysis, the problem of segregation measurement of dendrites of large-scale thermal work mold steel is solved, and efficient and accurate tissue quality evaluation and product performance improvement are achieved.
Patent Information
- Application Number
- CN202411479905.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to effectively measure dendrite segregation of large-scale thermal work mold steel, resulting in the inability to accurately evaluate the tissue quality and product performance.
A simple method, including heat treatment, sample preparation, chemical corrosion and scanning electron microscopy analysis, was used to calculate the dendrites segregation coefficient K by nitric alcohol solution corrosion and scanning electron microscopy measurement.
This method does not require complex corrosion agents, the process is simple and the success rate is high. It can clearly observe cross-tree dendrites, accurately measure dendrites segregation coefficient K, and promote product quality improvement.
Smart Images

Figure CN119510471A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallographic analysis, in particular to a method for measuring dendrite segregation of large ingot hot working die steel. Background Art
[0002] The main load-bearing components such as the main beams and landing gears of the new generation of aircraft, as well as the die forgings for high-end equipment such as engine blades, are developing towards the trend of "large-scale, integrated, precise, near-net-shape, and low-cost", which in turn requires the hot working dies to be larger. At this time, large-ingot die steel came into being, and the demand is increasing year by year.
[0003] The large-scale mold steel has put forward new requirements for technological innovation. The cooling rate of large ingot casting process is slow, and the element segregation becomes more serious accordingly, and more secondary carbides are precipitated during the cooling process, especially for steels such as Cr-Mo-V hot working die steel. Because the steel itself contains more carbide-forming elements Cr, Mo, and V, and the large ingot casting solidification cooling process takes a long time, pearlite structure and a large number of secondary carbides precipitate and aggregate at the 1 / 2 radius and core of the steel ingot, which makes it impossible to observe the cross-dendritic structure after corrosion by conventional methods, but presents a river-like organizational morphology, so that the dendrite segregation coefficient K cannot be counted.
[0004] Therefore, there is a need in the prior art for an improved method for measuring dendrite segregation for large ingot hot working die steel. Summary of the invention
[0005] In view of this, the purpose of an embodiment of the present invention is to propose a dendrite segregation measurement method for large ingot hot working die steel, which does not require the use of corrosive agents with complex proportions, has a simple process and a high success rate, is suitable for the quality assessment of cast structures, and promotes product quality improvement.
[0006] Based on the above purpose, an embodiment of the present invention provides a method for measuring dendrite segregation for large ingot hot working die steel. S1 heat treatment: prepare the steel billet sample and perform heat treatment in a heating furnace; S2 Sample preparation: Prepare the heat-treated sample into a metallographic sample, grind and polish the metallographic sample until the observation surface is bright and scratch-free, wash it with clean water, immerse it in an alcohol solution for ultrasonic cleaning, and dry it for later use; S3 Chemical corrosion: Place the metallographic sample in a beaker filled with nitric acid alcohol solution for corrosion for 12 to 18 seconds. When the surface of the metallographic sample shows light gray lines, pause for 2 to 3 seconds, take out the sample and rinse and dry it; S4 measurement and analysis: Use a scanning electron microscope to measure. In the same field of view of the electron microscope, randomly select 10 to 12 points on the dendrite trunk and between the dendrites. Use point scanning to measure the mass percentage of the element to be measured at each point, and calculate the segregation coefficient K.
[0007] In some embodiments, in S1, the steel billet includes, by mass percentage: C: 0.38% to 0.43%; Si: 0.80% to 1.00%; Mn: 0.20% to 0.40%; Cr: 4.75% to 5.25%; V: 0.30% to 0.80%; Mo: 1.10% to 1.45%; the remainder is Fe and unavoidable impurities.
[0008] In some embodiments, in S1, the heat treatment includes: heating the sample to 980°C±20°C in a furnace, keeping the temperature for 20-25 minutes, and cooling the sample to room temperature with oil after the sample is taken out of the furnace.
[0009] In some embodiments, in S2, during grinding, 200 mesh, 400 mesh, 800 mesh, and 1000 mesh water sandpaper are used for grinding respectively.
[0010] In some embodiments, in S2, during polishing, a 1 μm metallographic polishing agent is used for polishing.
[0011] In some embodiments, in S2, the time for cleaning the metallographic sample using ultrasonic wave is 3 to 5 minutes.
[0012] In some embodiments, in S3, during chemical etching, a 4% nitric acid alcohol solution is used, measured by mass percentage, and the nitric acid alcohol solution at least covers the top of the metallographic sample by 3-5 mm.
[0013] In some embodiments, in S3, when blow-drying, a hair dryer is used to blow dry at an angle of 45° toward the surface.
[0014] In some embodiments, in S4, the segregation coefficient K=the average mass percentage of the inter-dendritic element / the average mass percentage of the dendrite dry element.
[0015] In some embodiments, in S2, the diameter of the metallographic sample is ≤30 mm.
[0016] The present invention has at least the following beneficial technical effects: The present invention combines conventional heat treatment process with the most common 4% nitric acid alcohol corrosive agent, has a simple process and a success rate of 100%; compared with the prior art, it does not require extremely stringent requirements on the formula, action time and action temperature of the corrosive agent, and is simple and practical. After the heat treatment process provided by the present invention is applied to large ingot hot working die steel, the developed cross dendrites of the large ingot hot working die steel can be clearly observed, which is convenient for measuring the dendrite segregation coefficient K value. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0018] Figure 1 A schematic diagram of an embodiment of a method for measuring dendrite segregation of large ingot hot working die steel provided by the present invention; Figure 2 The river pattern matrix tissue diagram of Example 1 provided by the present invention; Figure 3 The cross-dendritic matrix organization diagram of Example 1 provided by the present invention; Figure 4 The scanned image of the dendrite dry point of Example 1 provided by the present invention; Figure 5 The interdendritic point scan diagram of Example 1 provided by the present invention; Figure 6 The river pattern matrix tissue diagram of Example 2 provided by the present invention; Figure 7 This is a cross-dendritic matrix organization diagram of Example 2 provided by the present invention. DETAILED DESCRIPTION
[0019] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.
[0020] The terms "including" and "having" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions; the terms "first", "second", etc. in the specification and claims of the present invention or the above-mentioned drawings are used to distinguish different objects rather than to describe a specific order. "Multiple" means two or more, unless otherwise clearly and specifically defined.
[0021] In addition, reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0022] like Figure 1The present invention provides a method for measuring dendrite segregation of large ingot hot working die steel, comprising: S1 heat treatment: prepare the steel billet sample and perform heat treatment in a heating furnace; S2 Sample preparation: Prepare the heat-treated sample into a metallographic sample, grind and polish the metallographic sample until the observation surface is bright and scratch-free, wash it with clean water, immerse it in an alcohol solution for ultrasonic cleaning, and dry it for later use; S3 Chemical corrosion: Place the metallographic sample in a beaker filled with nitric acid alcohol solution for corrosion for 12 to 18 seconds. When the surface of the metallographic sample shows light gray lines, pause for 2 to 3 seconds, take out the sample and rinse and dry it; S4 measurement and analysis: Use a scanning electron microscope to measure. In the same field of view of the electron microscope, randomly select 10 to 12 points on the dendrite trunk and between the dendrites. Use point scanning to measure the mass percentage of the element to be measured at each point, and calculate the segregation coefficient K.
[0023] The method of the invention comprises four stages: heat treatment, sample preparation, chemical corrosion and SEM-EDS component analysis and data processing.
[0024] The chemical composition of the steel billet is as follows by mass percentage: C: 0.38% ~ 0.43%; Si: 0.80% ~ 1.00%; Mn: 0.20% ~ 0.40%; Cr: 4.75% ~ 5.25%; V: 0.30% ~ 0.80%; Mo: 1.10% ~ 1.45%; the remainder is Fe and unavoidable impurities.
[0025] Further, in S1, heat treatment is performed: the sample is placed in a heating furnace, the temperature is raised to 980°C ± 20°C, the temperature is kept for 20-25 minutes, the sample is taken out of the furnace, and the sample is oil-cooled to room temperature.
[0026] Since the presence of secondary fine carbides and pearlite structure directly affects the observation of dendrite morphology, the secondary precipitated fine carbides can be fully dissolved back as the furnace temperature rises, and the pearlite structure is re-austenitized. The cooling method adopts a faster oil cooling method to transform it into a martensite structure that does not affect the observation of dendrite morphology. The heating temperature is controlled at 980℃±20℃ and the holding time is only 20-25min, which is still within the quenching temperature range and is far from the diffusion annealing temperature range. Therefore, the heat treatment using this method will not affect the changes in dendrite morphology and size, nor will it affect the changes in the content of elements in the dendrite stem and between dendrites.
[0027] Further, in S2, sample preparation: the heat-treated sample is prepared into a metallographic sample according to the GB / T13298 metallographic microstructure inspection method, the metallographic sample is polished with 200 mesh, 400 mesh, 800 mesh and 1000 mesh water sandpaper, and then polished with 1 μm metallographic polishing agent until the observation surface is bright and scratch-free; after the prepared sample is thoroughly cleaned with clean water, it is immersed in an alcohol solution, the metallographic sample is cleaned with ultrasound for 3-5 minutes and then dried for use.
[0028] Further, in S3, chemical corrosion: pour an appropriate amount of 4% nitric acid alcohol solution into the beaker to ensure that the solution can cover the sample by 3-5mm; use bamboo clips to place the cleaned sample into the beaker containing nitric acid alcohol solution for corrosion. The corrosion process needs to be observed in real time and the solution should be shaken appropriately for 12-18s. When the surface of the sample shows light gray lines, pause for 2-3s, immediately take out the sample and rinse the surface with clean water, and finally use a hair dryer to dry the surface at an angle of 45° outward; the pause time should not be too long to avoid excessive corrosion.
[0029] Furthermore, in S4, SEM-EDS component analysis and data processing: within the same field of view of the SEM scanning electron microscope, preferably, 10 points are randomly selected on the dendrite trunk and between dendrites, and the mass percentage of the element to be measured at each point is measured using point scanning, and the segregation coefficient K = the average mass percentage of the element between dendrites / the average mass percentage of the element on the dendrite trunk.
[0030] The results of the embodiment show that after the heat treatment process provided by the present invention is applied to large ingot hot working die steel, the developed cross dendrites of the large ingot hot working die steel can be clearly observed, which is convenient for measuring the dendrite segregation coefficient K value.
[0031] The following is further described in conjunction with specific embodiments.
[0032] Example 1 A steel plant produces 15t hot working die steel electroslag ingots. Table 1 is a list of chemical composition values of Example 1 of the present invention. A sample at 1 / 2 radius of the A end of the electroslag ingot (after cutting off the riser) was taken for analysis.
[0033] Table 1 Chemical composition of main elements in Example 1 (mass percentage %) Serial number C Si Mn Cr Mo V Example 1 0.40 0.98 0.36 5.25 1.15 0.56 1. Heat treatment: Place the sample in a heating furnace, heat it to 985°C, keep it warm for 25 minutes, take it out of the furnace, and oil cool it to room temperature.
[0034] 2. Sample preparation: The heat-treated metallographic sample is polished with 200 mesh, 400 mesh, 800 mesh and 1000 mesh water sandpaper, and then polished with 1μm metallographic polishing agent until the observation surface is bright and scratch-free; after the prepared sample is thoroughly cleaned with clean water, it is immersed in an alcohol solution, and the metallographic sample is cleaned with ultrasonic wave for 5 minutes and then dried for use.
[0035] 3. Chemical corrosion: Pour an appropriate amount of 4% nitric acid alcohol solution into a beaker, ensuring that the solution can cover the sample by 3-5mm; use bamboo clips to place the cleaned sample into the beaker containing nitric acid alcohol solution for corrosion. The corrosion process needs to be observed in real time and the solution should be shaken appropriately for 15 seconds. When the surface of the sample shows light gray lines, pause for 3 seconds, immediately remove the sample and rinse the surface with clean water, and finally use a hair dryer to dry it at an angle of 45° to the surface. Observe the organization under an OM optical microscope. Figure 2 The river pattern matrix structure diagram of the sample of Example 1 without heat treatment is shown in FIG. Figure 3 The strong cross-dendritic matrix structure diagram of the sample of Example 1 after heat treatment is shown.
[0036] 4. SEM-EDS composition analysis and data processing: In the field of view of the SEM scanning electron microscope at 700 times, 10 points were randomly selected between dendrites and dendrite stems, and 10 points were randomly selected between dendrite stems and dendrites, using point scanning, such as Figure 4 , Figure 5 As shown, the mass percentage of the measured elements at each point is measured, and the segregation coefficient K = the average mass percentage of the elements between the dendrites / the average mass percentage of the elements in the dendrite stem, and the results are shown in Table 2. Among them, C, Mn, Cr, Mo and V elements are enriched in the dendrites, and Si element is distributed more evenly between the dendrite stem and the dendrites.
[0037] Table 2 Segregation coefficient K of each element Serial number C Si Mn Cr Mo V Example 1 2.14 1.05 1.15 1.24 1.80 1.23 Example 2 1.85 0.92 2,16 1.11 1.25 1.40 Example 2 A steel plant produces 18t hot working die steel electroslag ingots. Table 3 is a list of chemical composition values of Example 2 of the present invention. A sample at the 1 / 2 radius of the H end of the electroslag ingot is taken for analysis.
[0038] Table 3 Chemical composition of main elements in Example 2 (mass percentage %) Serial number C Si Mn Cr Mo V Example 2 0.42 0.81 0.36 4.97 1.25 0.72 1. Heat treatment: Place the sample in a heating furnace, heat it to 1000℃, keep it warm for 20 minutes, take it out of the furnace, and cool it to room temperature with oil.
[0039] 2. Sample preparation: The heat-treated metallographic sample was polished with 200-mesh, 400-mesh, 800-mesh and 1000-mesh water-sandpaper, and then polished with 1μm metallographic polishing agent until the observation surface was bright and scratch-free; the prepared sample was thoroughly cleaned with clean water, immersed in an alcohol solution, and the metallographic sample was cleaned with ultrasonic wave for 4 minutes and then dried for use.
[0040] 3. Chemical corrosion: Pour an appropriate amount of 4% nitric acid alcohol solution into a beaker, ensuring that the solution can cover the sample by 3-5mm; use bamboo clips to place the cleaned sample into the beaker containing nitric acid alcohol solution for corrosion. The corrosion process needs to be observed in real time and the solution should be shaken appropriately for 16 seconds. When the surface of the sample shows light gray lines, pause for 2 seconds, immediately remove the sample and rinse the surface with clean water, and finally use a hair dryer to dry it at an angle of 45° to the surface. Observe the organization under an OM optical microscope. Figure 6 The river pattern matrix structure diagram of the sample of Example 2 without heat treatment is shown in FIG. Figure 7 The strong cross-dendritic matrix structure of the sample of Example 5 after heat treatment is shown.
[0041] 4. SEM-EDS composition analysis and data processing: In the field of view of the SEM scanning electron microscope at 700 times, 10 points were randomly selected on the dendrite trunk and between dendrites, and the mass percentage of the measured elements at each point was measured using point scanning. The segregation coefficient K = the average mass percentage of the elements between dendrites / the average mass percentage of the elements in the dendrite trunk. The results are shown in Table 2. Among them, C, Mn, Cr, Mo and V elements are enriched in the dendrites, and Si element is distributed more evenly between the dendrite trunk and the dendrites.
[0042] The above are exemplary embodiments disclosed in the present invention, but it should be noted that various changes and modifications may be made without departing from the scope disclosed in the embodiments of the present invention as defined in the claims. The functions, steps and / or actions of the method claims according to the disclosed embodiments described herein do not need to be performed in any particular order. In addition, although the elements disclosed in the embodiments of the present invention may be described or required in individual form, they may also be understood as multiple unless explicitly limited to the singular.
[0043] It should be understood that, as used herein, the singular forms "a", "an" are intended to include the plural forms as well, unless the context clearly supports an exception. It should also be understood that, as used herein, "and / or" refers to any and all possible combinations including one or more of the associated listed items.
[0044] The serial numbers of the embodiments disclosed in the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0045] A person skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the disclosure of the embodiments of the present invention (including the claims) is limited to these examples; under the concept of the embodiments of the present invention, the technical features in the above embodiments or different embodiments can also be combined, and there are many other changes in different aspects of the above embodiments of the present invention, which are not provided in detail for the sake of simplicity. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the embodiments of the present invention should be included in the protection scope of the embodiments of the present invention.
Claims
1. A method for measuring dendrite segregation of large ingot hot working die steel, characterized in that: include: S1 heat treatment: prepare the steel billet sample and perform heat treatment in a heating furnace; S2 Sample preparation: Prepare the heat-treated sample into a metallographic sample, grind and polish the metallographic sample until the observation surface is bright and scratch-free, wash it with clean water, immerse it in an alcohol solution for ultrasonic cleaning, and dry it for later use; S3 chemical corrosion: put the metallographic sample into a beaker filled with nitric acid alcohol solution for corrosion for 12 to 18 seconds. When the surface of the metallographic sample shows light gray lines, pause for 2 to 3 seconds, take out the sample and rinse and blow dry; S4 measurement and analysis: Use a scanning electron microscope to measure. In the same field of view of the electron microscope, randomly select 10 to 12 points on the dendrite trunk and between the dendrites. Use point scanning to measure the mass percentage of the element to be measured at each point, and calculate the segregation coefficient K.
2. The method for measuring dendrite segregation of large ingot hot working die steel according to claim 1, characterized in that: In S1, the steel billet includes, by mass percentage: C: 0.38% to 0.43%; Si: 0.80% to 1.00%; Mn: 0.20% to 0.40%; Cr: 4.75% to 5.25%; V: 0.30% to 0.80%; Mo: 1.10% to 1.45%; the remainder is Fe and unavoidable impurities.
3. The method for measuring dendrite segregation of large ingot hot working die steel according to claim 1, characterized in that: In S1, the heat treatment includes: heating the sample to 980°C±20°C in a furnace, keeping the temperature for 20-25 minutes, and oil cooling the sample to room temperature after being taken out of the furnace.
4. The method for measuring dendrite segregation of large ingot hot working die steel according to claim 1, characterized in that: In S2, during grinding, 200-mesh, 400-mesh, 800-mesh, and 1000-mesh water-sandpaper are used for grinding respectively.
5. The method for measuring dendrite segregation of large ingot hot working die steel according to claim 1, characterized in that: In S2, during polishing, a 1 μm metallographic polishing agent is used for polishing.
6. The method for measuring dendrite segregation of large ingot hot working die steel according to claim 1, characterized in that: In S2, the metallographic sample is cleaned using ultrasonic waves for 3 to 5 minutes.
7. The method for measuring dendrite segregation of large ingot hot working die steel according to claim 1, characterized in that: In S3, during chemical etching, a 4% nitric acid alcohol solution is used, measured by mass percentage, and the nitric acid alcohol solution at least covers the top of the metallographic sample by 3 to 5 mm.
8. The method for measuring dendrite segregation of large ingot hot working die steel according to claim 1, characterized in that: In S3, when blow-drying, use a hair dryer to blow dry at an angle of 45° toward the surface.
9. The method for measuring dendrite segregation of large ingot hot working die steel according to claim 1, characterized in that: In S4, the segregation coefficient K = the average mass percentage of the interdendritic elements / the average mass percentage of the dendrite dry elements.
10. The method for measuring dendrite segregation for large ingot hot working die steel according to claim 1, characterized in that: In S2, the diameter of the metallographic sample is ≤30 mm.
Citation Information
Cited By
Method for displaying grain boundary of high-carbon chromium bearing steel
CN119776832A